Behemoth / 2. - Westerfeld, Scott, (Leviathan trilogy ;, 2010)
Continues the story of Austrian Prince Alek who, in an alternate 1914 Europe, eludes the Germans by traveling in the Leviathan to Constantinople, where he faces a whole new kind of genetically-engineered warships.